THE CHALLENGE AND PROMISE OF CRITICAL PEDAGOGY IN THE NEW INFORMATION AGE: AN INTERVIEW WITH HENRY GIROUX - Henry Giroux (Ediciones Universidad de Salamanca, 2009)
In this interview Giroux explores the various emancipatory and authoritarian conceptualisations of education, underlining their political nature due to their opportunity to connect knowledge, authority and power. Critical education is understood to be the result of private battles, linked to specific communities, to available resources and the stories, identities and experiences of students. Giroux conceptualises education as a challenge, which attempts to take people beyond the world that they know. Thus forms of knowledge which make the extension of democratic culture become possible. However Giroux also analyses the reality in higher education, affected by a crisis of politics and of legitimacy, which makes the development of democratic principles difficult and imposes instrumental and commercial terms. Faced with this, the author requests that universities take on an active role in order to resolve problems in our societies, providing students with critical knowledge so as to respond to current anti-democratic trends.